Inhibitory neurons in the superior colliculus mediate selection of spatially-directed movements - Jaclyn Essig (Nature Portfolio, 2021)
Essig et al used a combination of behavior, optogenetics, neural recordings and modelling to directly examine the contribution of GABAergic superior colliculus neurons to the selection of opposing spatial targets. They demonstrated that these neurons do not locally suppress premotor output, suggesting that functional long-range inhibition instead plays a dominant role in spatial choice.